Scutellarin ameliorates ischemia/reperfusion-mediated endothelial dysfunction by upregulating cathepsin D expression to rescue autophagy-lysosomal function - Zhuang, Qizhen; Chen, Lu; Wu, Wanqian; Wang, Qing; Kang, Chunmin; Xiong, Yujuan; Huang, Xianzhang (Frontiers in Pharmacology, 2025)
BackgroundEndothelial dysfunction-induced microcirculation impairment and the no-reflow phenomenon are the leading causes of cardiac ischemia/reperfusion (I/R) injury. There is an urgent need to elucidate the underlying mechanism of I/R-mediated endothelial dysfunction and to identify effective drugs for treatment. Scutellarin (SCU), a flavonoid compound, has been extensively studied because of its various pharmacological properties, including its potent protective effects on the cardiovascular system. However, the anti-endothelial dysfunction efficacy and mechanisms of action of SCU have not been investigated.Approach and resultsAn in vivo I/R injury model was established using coronary artery ligation and release. An oxygen-glucose deprivation/oxygen-glucose resupply (OGD/OGR) approach was used to establish an in vitro I/R injury model. We evaluated the effects of SCU on endothelial dysfunction under I/R conditions, both in vivo and in vitro. SCU pretreatment promoted vasodilation and reperfusion of blood flow, inhibited myocardial injury and infarction, and improved cardiac function in I/R rats. Additionally, SCU inhibited cell membrane damage, reactive oxygen species (ROS) accumulation, inflammation, nitric oxide (NO) reduction, endothelin 1 (ET-1) elevation and increase in the expression levels of vascular endothelial growth factor (VEGF) and von willebrand factor (vWF) in endothelial cells. Mechanistically, SCU rescued the lysosomal flow and autophagic flux disrupted by I/R through upregulating cathepsin D (CTSD) levels. Knockdown of CTSD or treatment with the CTSD inhibitor pepstatin A (P.A) abrogated the protective effects of SCU on endothelial cells under I/R conditions.ConclusionWe demonstrated that SCU, via upregulation of CTSD levels in endothelial cells, rescued autophagy-lysosomal function and alleviated I/R-mediated endothelial dysfunction. Thus, SCU is a potential therapeutic drug for the prevention and treatment of cardiac I/R injury.